Polyacrylonitrile-based precursors and carbon fibers derived from advanced RAFT technology and conventional methods – The 1st comparative study. (December 2016) - Cai, Jackie Y.; McDonnell, Jill; Brackley, Colin; O'Brien, Lisa; Church, Jeffrey S.; Millington, Keith; Smith, Shaun; Phair-Sorensen, Nicole
Graphical abstract: Abstract: This paper reports on a significant advancement in carbon fiber precursor research. We have successfully applied reversible addition–fragmentation chain transfer (RAFT) technology to polyacrylonitrile (PAN) based carbon fiber precursor synthesis, and developed new PAN precursor polymers with a high molecular weight (Mn  > 300 K), while still maintaining a low polydispersity index (PDI) (<1.2). This desirable molecular profile has not been attainable until now. The paper also reports on the very first comparative study carried out for assessing the properties and performance of such a high molecular weight, low PDI precursor and its resultant carbon fiber against the conventional controls. In this comparative study, a control precursor polymer with a closely matching molecular weight and comonomer content was prepared by conventional free radical polymerization. Both of the RAFT mediated PAN (RAFT PAN) and control PAN precursor polymers were processed into precursor fibers and carbon fibers under identical conditions. The structures and properties of these fibers were characterized and evaluated. The results of this preliminary study have demonstrated a signifcant improvement in the rheological property of RAFT PAN polymer, and significant improvement in the mechanical properties of the precursor fiber and carbon fiber derived from the RAFT PAN precursor polymer.